The Jackson County War : Reconstruction and Resistance in Post-Civil War Florida - Weinfeld, Daniel R. (Book collections on Project MUSE., 2012)
The Jackson County War offers original conclusions explaining why Jackson County became the bloodiest region in Reconstruction Florida and is the first book-length treatment of the subject. From early 1869 through the end of 1871, citizens of Jackson County, Florida, slaughtered their neighbors by the score. The nearly threeyear frenzy of bloodshed became known as the Jackson County War. The killings, close to one hundred and by some estimates twice that number, brought Jackson County the notoriety of being the most violent county in Florida during the Reconstruction era. Daniel R. Weinfel.